Sensibilización de la experiencia literaria de los preadolescentes en la escuela a través de narrativas de la literatura universal - Sampedro Builes, Gilena María (Educación, Ciencias Humanas y Sociales, 2018)
This work delves into the problem of the type of literary content that is usually taken to school classrooms with preadolescent students, in which there is a tendency to moralize and to educate, a fact that discourages the autonomy that literature has when it comes talk about children's issues, but also about love, questions, adventures and misadventures of the adult world (for which they are being prepared), and deprives the student of the possibility of securing a more elaborate lexicon and a metaphorical-poetic language that could be learning by reading works of universal literature. Therefore, in the development of this deepening and considering the authors we will address, it will be reflected in these pages the reason why a literature for preadolescent students must be a literature with autonomy, not willing to catechize but to develop the imagination and the cognitive and critical capacity of the student from the sensitive experience of literary art